2013
DOI: 10.1007/s10815-013-9951-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower sperm DNA fragmentation after r-FSH administration in functional hypogonadotropic hypogonadism

Abstract: Purpose An observational clinical and molecular study was designed to evaluate the effects of the administration of recombinant human FSH on sperm DNA fragmentation in men with a non-classical form of hypogonadotropic hypogonadism and idiopathic oligoasthenoteratozoospermia. Methods In the study were included 53 men with a nonclassical form of hypogonadotropic hypogonadism and idiopathic oligoasthenoteratozoospermia. In all patients, sperm DNA fragmentation index (DFI), assessed by terminal deoxynucleotidyl tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 69 publications
(73 reference statements)
0
25
0
1
Order By: Relevance
“…Previous human studies demonstrated a positive effect of FSH therapy on ultrastructural sperm characteristics and DNA condensation (Bartoov et al, 1994;Baccetti et al, 1997Baccetti et al, , 2004Kamischke et al, 1998;Ben-Rafael et al, 2000;Piomboni et al, 2009). Moreover, recent studies showed that FSH therapy improves sperm DNA integrity in men with idiopathic oligoasthenozoospermia by reducing DNA fragmentation index (Palomba et al, 2011;Colacurci et al, 2012;Ruvolo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous human studies demonstrated a positive effect of FSH therapy on ultrastructural sperm characteristics and DNA condensation (Bartoov et al, 1994;Baccetti et al, 1997Baccetti et al, , 2004Kamischke et al, 1998;Ben-Rafael et al, 2000;Piomboni et al, 2009). Moreover, recent studies showed that FSH therapy improves sperm DNA integrity in men with idiopathic oligoasthenozoospermia by reducing DNA fragmentation index (Palomba et al, 2011;Colacurci et al, 2012;Ruvolo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our aim was to evaluate the effect of FSH treatment not only after the entire cycle of spermatogenesis (3 months) but also to test whether spermiogenesis (the last 1 month of spermatogenesis) would be also affected positively by the drug. Moreover, recent studies showed that FSH therapy improves sperm DNA integrity in men with idiopathic oligoasthenozoospermia by reducing DNA fragmentation index (Palomba et al, 2011;Colacurci et al, 2012;Ruvolo et al, 2013). In vitro studies on human germ cells showed that FSH stimulates meiosis II and round spermatid flagellum extrusion, whereas Testosterone potentiates FSH action and stimulates late spermatid differentiation (Sousa et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The labeling of DNA strand breaks (the terminal transferased UTP nick-end labeling (TUNEL) assay), Annexin V-propidium iodide assay and Sperm Chromatin Structure Assay are used for the detection and quantification of apoptosis in sperm (DNA fragmentation) (Erenpreisa et al 2002, Ricci et al 2002, Oosterhuis and Vermes 2004, Mahfouz 2009, Rylander et al 2009, Gatimel et al 2013, Gomez-Lopez et al 2013, Ruvolo et al 2013.…”
Section: Evaluation Of Sperm Morphologymentioning
confidence: 99%
“…observed that rhFSH treatment increases sperm DNA condensation in idiopathic infertile men (Kamischke et al ., ). In an our experience, we found that rhFSH improves sperm DNA integrity in iOAT men who show increased sperm DFI values (Colacurci et al ., ) confirmed by a later study (Ruvolo et al ., ).…”
Section: Discussionmentioning
confidence: 97%